Faktor-Faktor Yang Mempengaruhi Return Saham Perusahaan Manufaktur Pada Bursa Efek Indonesia - Jensen, Elizabeth Sugiarto Dermawan (Jurnal Paradigma Akuntansi, 2022)
This research aims at how the effect of profitability, solvability, liquidity, and firm size on stock return onmanufacture company listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 69 companies. Data processing techniques usingmultiple regression analysis what helped by SPSS program (Statistical Product and Service Solution) for Windows released 22 and Microsoft Excel 2016. The results of this study indicate that profitability have a positive and significant influence on stock return, Solvability, liquidity, and firm size do not have significant influence on stock return. The implication of this study is the need to increase financial performance that will increase stock return which will bring a good signal for investors.